Implementasi Kebijakan Makan Bergizi Gratis (MBG) (Studi Kasus pada SMA Swasta Lancang Kuning Kota Dumai) - Erinaldi; Ananta, Dhea Nabila Putri; Nadhira, Syarifah (LPPM STIA Lancang Kuning Dumai, 2025)
Balanced nutrition from school age is essential to support health, learning ability, and human resource quality. The Free Nutritious Meal (MBG) program is a government policy aimed at ensuring children’s right to adequate nutrition and improving education quality. This study analyzes the implementation of the MBG program at SMA Swasta Lancang Kuning Dumai based on George C. Edwards III’s implementation theory, focusing on communication, resources, implementers’ disposition, and bureaucratic structure. A descriptive qualitative method was used through interviews, observation, and documentation. The findings show that the MBG program positively impacts students’ motivation, discipline, and well-being but faces challenges in communication consistency, facility supervision, menu variety, and food distribution timeliness. Recommendations include strengthening coordination, standardizing procedures, improving quality control, and increasing active participation from schools and students to ensure the program’s effectiveness and sustainability.